Diachronic patterns of usage of no doubt in the English Historical Book Collection (EEBO, ECCO and EVANS) - Smith Chris A. (ExELL (Explorations in English Language and Linguistics))
This study offers a collocate analysis of the modal marker no doubt (ND) in the EEBO, ECCO and EVANS combined corpora using Sketch Engine. The purpose is to determine the diachronic patterns of usage of ND, and secondly to compare results with the conclusions of existing diachronic pragmatic studies of modal markers. The first step identified five patterns of behaviour based on AM score in decreasing order of frequency: 1 – NDB (no doubt but); 2 – TISND (there is no doubt); 3 – MND (make no doubt); 4 – (ND (parenthetical use); 5 – Ndont (no doubt on’t). The second step consisting in partitioning of the corpus following Hilpert and Gries (2016) produced 3 distinct periods based on EHBO data (1580-1669, 1670-1759, 1760-1799). The findings showed that the relative usage of ND for each period remained remarkably consistent, especially the persistence of non-grammaticalized behaviours MND and TISN. The two major disparities, concerning NDont and parenthetical (ND, were shown to be of likely significance for the changing pragmatic behaviour of ND, which further diachronic study may be able to ascertain.